Lipophilic Gold Grating for SERS Detection of Biological Objects; Proceedings; Vol. 1, iss. 4 - Guselnikova O. A. Olga Andreevna; Hrobonova K.; Postnikov P. S. Pavel Sergeevich; Lyutakov O. Oleksii; Svorcik V. Vaclav (2017, 2017)
Title screen